Seroprevalences of Babesiea species in cattle in Elazig, Malatya and Tunceli provinces - Aktas, M; Dumanli, N; Karaer, Z; Çakmak, A; Sevgili, M (Scientific Technical Research Council Turkey, 2001)
This study was carried out in cattle in Elazig, Malatya and Tunceli provinces between May 1997 and March 1998 to determine the seroprevalence of Babesia species. Serum samples were collected from a total of 741 cattle in Elazig, Malatya, Tunceli and vicinities. Serum antibodies against Babesia bigemina, Babesia bovis and Babesia divergens were investigated by Indirect Fluorescence Antibody (IFA) test. in addition, peripheral blood smears were prepared and examined under a microscope. Antibodies were detected in 91 (31.9%) of 285 cattle against B. bigemina, in 4 (1.4%) against B. bovis and in 10 (3.5%) against B. divergens in Elazig and vicinity. Antibodies were determined in 21 (7.1%) of 292 cattle against B. bigemina and 2 (0.6%) against B. divergens in Malatya and vicinity. No antibodies against B. bovis were detected in the of serum of animals collected in this area. Antibodies were determined in 12 (7.3%) of 164 cattle against B. bigemina, 1 (0.6%) against B. bovis and 2 (1.2%) against B. divergens in Tunceli and vicinity. In the microscopic examination of peripheral blood smears, Babesia sp. were observed in 4 (1.4%) and 2 (0.6%) cattle in Elazig and Malatya, respectively. These cattle also had antibody reaction to B bigemina.. Babesia sp. were not seen in the examinations of blood smears of cattle in Tunceli province.
Keywords: Babesia; serology; IFA; cattle